Analysis of Factors Influencing Purchase Decisions on Tokopedia in Bandung City - Cristalia Gomies, Vieren; Sibarani, Mentiana (Green Publisher Indonesia, 2024)
This study aims to analyze the factors that influence consumer purchasing decisions on the Tokopedia e-commerce platform in Bandung City. The factors evaluated include product quality, price, platform ease of use, consumer trust, promotion, and customer service. This research uses a quantitative approach with a survey method distributed to consumers in Bandung City who have made purchases on Tokopedia. The data were analyzed using multiple linear regression to determine the effect of each factor on purchasing decisions. The results showed that product quality, price, and consumer trust have a significant influence on purchasing decisions, while other factors such as ease of use of the platform, promotions, and customer service have a lower but still important influence. The findings provide insights for e-commerce players in improving marketing and operational strategies to attract more consumers.